2022
DOI: 10.1002/oby.23660
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting and protein pacing are superior to caloric restriction for weight and visceral fat loss

Abstract: Objective: This study compared intermittent fasting and protein pacing (IF-P) versus a heart-healthy caloric restriction (CR) diet, matched for energy intake and physical activity energy expenditure, on body weight, total and visceral fat mass, and cardiometabolic health outcomes in adults with obesity. Methods: IF-P (n = 21) and CR (n = 20) were assessed pre-(week 0), mid-(week 5), and post-(week 9) intervention.Results: Both groups reduced (p < 0.05) weight, total and visceral fat mass, blood pressure and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Weight loss and fat loss are more pronounced in those with overweight or obesity compared to normal weight controls. This rapid review evidences that IF and CER have comparable weight loss results; however, new evidence is emerging that in some cases IF may be more effective 52 . Therefore, IF could be recommended by practitioners as an alternative diet strategy for those who find CER difficult to maintain.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Weight loss and fat loss are more pronounced in those with overweight or obesity compared to normal weight controls. This rapid review evidences that IF and CER have comparable weight loss results; however, new evidence is emerging that in some cases IF may be more effective 52 . Therefore, IF could be recommended by practitioners as an alternative diet strategy for those who find CER difficult to maintain.…”
Section: Discussionmentioning
confidence: 91%
“…This rapid review evidences that IF and CER have comparable weight loss results; however, new evidence is emerging that in some cases IF may be more effective. 52 Therefore, IF could be recommended by practitioners as an alternative diet strategy for those who find CER difficult to maintain. Most studies found some reduction in fat mass and none found an increase; therefore, those wishing to reduce fat mass could undertake IF.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term caloric restriction has been demonstrated to induce favorable cardiovascular effects, namely reductions in blood pressure and improved lipid profile (Fontana et al., 2004; Holloszy & Fontana, 2007; Jakobsdottir et al., 2016; Nicoll & Henein, 2018; Walford et al., 2002), even in nonobese (Ravussin et al., 2015), though intermittent fasting (IF) may elicit similar effects (Arciero et al., 2022; Yang et al., 2021). Long‐term CR of ca.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight reduction is normally associated with a loss of both fat‐free mass (25–30%) and fat mass (70–75%) 25,26 . Unfortunately, we did not measure body composition.…”
Section: Discussionmentioning
confidence: 99%